Kupffer cells control neonatal hepatic metabolism via Igf1 signaling - Makdissi, Nikola; Hirschmann, Daria J.; Frolov, Aleksej; Sado, Inaam; Bennühr, Bastian; Nikolka, Fabian; Cheng, Jingyuan; Blank-Stein, Nelli; Viola, Maria Francesca; Yaghmour, Mohamed; Arnold, Philipp; Bonaguro, Lorenzo; et al. (Development, 2026)
During perinatal development, liver metabolism is tightly regulated to ensure energy supply for the newborn. Before birth, glycogen is stored in hepatocytes and later metabolized to glucose, meeting neonatal energy demands. Shortly after birth, lipogenesis begins, driven by transcriptional activation of enzymes involved in fatty acid oxidation. These processes are thought to be largely regulated by systemic insulin and glucagon levels. However, the role of liver-derived local factors in neonatal hepatocyte metabolism remains unexplored. Kupffer cells (KCs), the liver's resident macrophages, colonize the fetal liver early in embryogenesis and support liver metabolism in adulthood. Yet whether KCs influence neonatal hepatocyte metabolism is unknown. Using conditional knockout mouse models targeting macrophages, we demonstrate that yolk sac-derived KCs play a crucial role in hepatocyte glycogen storage and function by regulating the tricarboxylic acid cycle, a role monocyte-derived KC-like cells cannot substitute. Newborn pups lacking yolk sac-derived KCs mobilize glycogen more rapidly, a process in part regulated by insulin-like growth factor 1 (Igf1) production. Our findings identify KCs as major source of Igf1, with local production essential for balanced hepatocyte metabolism at birth.
CRIS-Team Scopus Importer:2026-02-06
Keywords: Hepatocytes; Igf1; Kupffer cell; Liver development; Macrophage